Associations between Accommodative Facility, Age, and Refractive Errors in Early, Older Adolescent Myopes and Emmetropes. Issue 1 (31st March 2023) - Ramamurthy, Dharani; Radhakrishnan, Hema; Pardhan, Shahina
Background: Accommodative functions are known to differ between myopes and emmetropes. It is not known whether accommodative facility differs at near between younger adolescent and older adolescent myopes and emmetropes. Aim: To examine whether accommodative facility differs at near between younger and older adolescent myopes and emmetropes. Methods: 119 participants aged between 11–21 years were recruited. Refractive error was measured using cycloplegic retinoscopy. Near monocular accommodative facility was measured for 60 seconds, using a +2.00D/–2.00D handheld flipper and N6 print at 40 cm. Participants were classified into two age groups: (i) younger adolescents (range: 11–14 years) and (ii) older adolescents (range: 15–21 years). The criterion applied to define myopia was spherical equivalent refraction: ≥–0.50D) and spherical equivalent refraction: –0.25D to +0.75D) for emmetropia. Univariate Analysis of Variance was carried out to analyze the interaction of age groups and refractive groups on near accommodative facility. Results: Near monocular accommodative facility was significantly lower (p = 0.003) in younger adolescents (5.87 ± 3.72 cpm) compared to older adolescents (8.11 ± 4.11 cpm), indicating age as a significant main effect (F1, 115 = 13.44; p = 0.0001). Younger adolescent emmetropes (4.77 ± 2.05 cpm, p = 0.005) and younger adolescent myopes (6.48 ± 4.12 cpm, p = 0.022) had significantly lower monocular near accommodative facility compared to older adolescent emmetropes (9.52 ± 3.27 cpm), but did not show any difference when compared to older adolescent myopes (p > 0.05). This indicates a significant association linking age and refractive error to near accommodative facility (F1, 115 = 4.60; p = 0.03). Conclusion: Younger adolescent myopes and younger adolescent emmetropes had reduced monocular near accommodative facility than older adolescent emmetropes, but not when compared to older adolescent myopes.